Rola kobiet w sufizmie. Kobiece naśladowczynie Zakonu Mevlevi i ich aktywny udział w rytuale Sema - Mandziarz-Kuźmiński , Milda (Facta Simonidis, 2014)
Sema ritual identified with Rumi Mevlana’s order, known as Mevlevi Religion of Love, has been attracting people from different cultures from all over the world for centuries. Mevlevi followers are noticeably growing in number in the West, where their great engagement is well visible. Sema, which is a mystic dancing ritual known from the 13th century, represents man’s spiritual journey to Perfection through mind and love. Mevlevi as one of the most-known Sufi orders was exceptional for Rumi’s recognition of spiritual beauty and wisdom of women. Mevlana was accepting and teaching men and women alike, as he said that it is not the body but the soul that is important. He taught that all humans are equal and are united in their faith and love. Many female Sufis decided to fallow Mevlana’s teachings practicing sema that aims at “Unity with God”, truly convinced that they found their place within Islamic world. Women, who had noticeable role in the process of spreading this mystical concept have been playing multiple roles, i.e.: poets, musicians, and sometimes even pirs, becoming “the voice” of feminine Muslim society.